Anak Sebagai Korban Tindak Pidana Perdagangan Orang Menurut Undang-Undang No. 35 Tahun 2014 - Gede Agus Sukawantara; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Warmadewa Press, 2020)
Children are a mandate and a gift from God Almighty. Dignity as a human being is also inherent in them. Children are the potential successor and young generation who carry forward the ideals of the nation's struggle. They have a strategic role and special characteristics that ensure the continuity of the nation and state in the future. In order for each child to be able to bear this responsibility in the future, she/he needs to have the widest possible opportunity to grow and develop optimally, physically, mentally, socially, and nobly. Therefore, it is necessary to make efforts to protect the welfare of children by providing guarantees for the fulfillment of their rights as well as treatment without discrimination. This research was conducted with the aim of describing how the legal protection of children as victims of trafficking in persons based on Law Number 35 of 2014 concerning Child Protection and how the sanctions against the perpetrators of child trafficking. The research method used in this research was normative legal research. The results of this study indicated that legal protection for children as victims of trafficking in persons based on Law Number 35 of 2014 concerning Child Protection includes the protection of dignity, as well as recognition of human rights possessed by children based on legal provisions of abuse. In addition, the sanctions against the perpetrators of child trafficking are regulated in Law Number 21 of 2007 concerning the Eradication of the Crime of Trafficking in Persons.